Benzoic acid-4-{(1E)-[(E)-2-(pyridin-4-ylmethylidene)hydrazin-1-ylidene]methy l}pyridine (2/1) - Arman, H.D.; Kaulgud, T.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title co-crystal, C12H10N4 center dot 2C(7)H(6)O(2), the complete 4-pyridinealdazine molecule is generated by a crystallographic centre of inversion. In the crystal, molecules are connected into a three component aggregate via O-H center dot center dot center dot N hydrogen bonds. As both the benzoic acid [O-C-C-C torsion angle = 174.8 (2)degrees] and 4-pyridinealdazine (r.m.s. deviation of the 16 non-H atoms = 0.041 angstrom) molecules are almost planar, the resulting three-component aggregate is essentially planar. The crystal packing comprises layers of the three-component aggregates of alternating orientation stacked along the b axis; the connections between the molecules are of the types C-H center dot center dot center dot pi and pi-pi [pyridine-benzene centroid-centroid distance = 3.787 (4) angstrom].